2016
DOI: 10.1016/j.jvs.2014.05.042
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of the accessory renal arteries after endovascular repair of common iliac artery aneurysm using kissing stent grafts

Abstract: Exclusion of the accessory renal arteries (ARAs) is required during endovascular aneurysm repair if they arise from the sealing zone or aneurysm sac. Here, we report a case of successful endovascular treatment for a common iliac artery aneurysm located close to the aortic bifurcation and associated with nephrotic syndrome in a 51-year-old man. The bilateral ARAs were successfully preserved using kissing stent grafts. During surgery, the proximal ends of endografts inserted from the bilateral femoral arteries w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Hosaka et al had the same opinion and reported an ARA preservation technique during endovascular therapy. 5 …”
Section: Discussionmentioning
confidence: 99%
“…Hosaka et al had the same opinion and reported an ARA preservation technique during endovascular therapy. 5 …”
Section: Discussionmentioning
confidence: 99%